2015
DOI: 10.1378/chest.15-0264
|View full text |Cite
|
Sign up to set email alerts
|

Lung Density Changes With Growth and Inflation

Abstract: BACKGROUND:With body growth from childhood, the lungs can enlarge by either increasing the volume of air in the periphery (as would occur with inspiration) or by increasing the number of peripheral acinar units. In the former case, the lung tissue density would decrease with infl ation, whereas in the latter case, the lung density would be relatively constant as the lung grows. To address this fundamental structural issue, we measured the CT scan density in human subjects of widely varying size at two diff ere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…The lung density of the proposed phantom was comparable to the density of the human lung that was reported in another study . Robert et al .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The lung density of the proposed phantom was comparable to the density of the human lung that was reported in another study . Robert et al .…”
Section: Discussionsupporting
confidence: 85%
“…The lung density of the proposed phantom was comparable to the density of the human lung that was reported in another study. 39 Robert et al reported that the mean lung densities for nonsmokers were À836 HU for males (63 people) and À811 HU for females (51 people). 39 These values are similar to the density of our phantom (mean À813.24 HU in the decompressed state for the baseline breath-hold CT scan).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When lung tissue is destroyed, CT density decreases and the extent of emphysema can be quantified across the whole lung. Although people with larger lungs have bigger alveoli as assessed by CT density (Brown, et al, 2015), the magnitude of density changes in emphysema are far greater than the differences that would be seen between healthy large and small lungs. While decreased CT density has been shown in animal models of emphysema, this is not widely utilized.…”
Section: B Mouse Models Of Emphysemamentioning
confidence: 99%
“…The method normally used in preclinical models is to quantify changes in the postmortem histology, an approach clearly not appropriate for humans. The common metric is based on the mean distances between septal walls, but like alveolar size assessed by CT density (Brown, Wise, Kirk, Drummond and Mitzner, 2015), this metric also increases with lung volume (Hsia, et al, 2010). Thus in both human and animal models, it is essential to measure the lung volume changes with emphysema.…”
Section: B Mouse Models Of Emphysemamentioning
confidence: 99%